Mediation ResearchMediation Research, by Kressel Kenneth, Pruitt Dean G. and Associates. San Francisco, CA: Jossey-Bass, 1989, 457 pp., $32.95, cloth. - Cohen, Cynthia F. (Academy of Management Review, 1990)
The article presents a review of the book ?Mediation Research,? by Kenneth Kressel.